2021
DOI: 10.1177/11779322211055285
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variants Assessing Crohn’s Disease Pattern in Pediatric Inflammatory Bowel Disease Patients by a Clinical Exome Survey

Abstract: Background: Inflammatory bowel diseases (IBDs) are complex, multifactorial disorders that comprise Crohn’s disease (CD) and ulcerative colitis (UC). Recent discoveries have brought much attention to the genetic predisposition of patients with IBD. Here we evaluate the interaction between IBD genetic risk factors susceptibility and CD occurrence in an IBD pediatric patient population, performing a clinical exome survey. Methods: From February 2018 to April 2019, we collected blood samples from 7 pediatric patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…21 In a paediatric population, the gene clusters of NOD2 and autophagy-related 16 like 1 (ATG16L) demonstrated variants (rs2066844 and rs2241880), as strong risk factors for CD. 22 In a Malaysian cohort, polymorphisms in the autophagy-related 16 like 2 (ATG16L2) gene and long intergenic non-protein coding ribonucleic acid (RNA) 8234 (LINC00824) were shown to have a high risk of CD development. 23 A study assessed the contribution of gene variants to the IBD among Arab Muslims, Ashkenazi Jews, and the Druze population.…”
Section: Genetic Determinants Of Monogenic Ibdmentioning
confidence: 99%
“…21 In a paediatric population, the gene clusters of NOD2 and autophagy-related 16 like 1 (ATG16L) demonstrated variants (rs2066844 and rs2241880), as strong risk factors for CD. 22 In a Malaysian cohort, polymorphisms in the autophagy-related 16 like 2 (ATG16L2) gene and long intergenic non-protein coding ribonucleic acid (RNA) 8234 (LINC00824) were shown to have a high risk of CD development. 23 A study assessed the contribution of gene variants to the IBD among Arab Muslims, Ashkenazi Jews, and the Druze population.…”
Section: Genetic Determinants Of Monogenic Ibdmentioning
confidence: 99%
“…IBDs are multifactorial diseases that depend on the complex interplay between host genotype, environment, microbiome, and immune system. [1][2][3][4][5] The incidence of pediatric IBD (PIBD) has increased rapidly during the past decades, especially in countries where the incidence used to be low. 6 On the basis of 2 large US claims databases, the prevalence of PIBD more than doubled from 33 per 100 000 population in 2007 to 77 in 2016.…”
Section: Pediatric Inflammatory Bowel Diseasementioning
confidence: 99%
“…Combined genome wide association studies data from >25 000 patients have revealed >200 loci that increase the risk for either CD, UC, or (for the majority of loci) both. 1,82,83 The candidate genes that map to these loci are involved in a diverse array of cellular functions, including the response to cellular stress, epithelial barrier integrity, and the innate immune response to bacterial molecules. 84 This extensive body of research suggests that IBD pathogenesis may originate from dysfunction in 1 of a great many interconnected and codependent molecular pathways that operate in conjunction to maintain immune homeostasis in the intestinal tract.…”
Section: Can Ibd Be Prevented In Children At Familial Risk?mentioning
confidence: 99%